2017
DOI: 10.3389/fnbot.2017.00044
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Sub-functions for Control of Assistive Wearable Robots

Abstract: A primary goal of comparative biomechanics is to understand the fundamental physics of locomotion within an evolutionary context. Such an understanding of legged locomotion results in a transition from copying nature to borrowing strategies for interacting with the physical world regarding design and control of bio-inspired legged robots or robotic assistive devices. Inspired from nature, legged locomotion can be composed of three locomotor sub-functions, which are intrinsically interrelated: Stance: redirecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(91 reference statements)
2
8
0
2
Order By: Relevance
“…8 shows clear reductions in thigh biarticular muscles activities, obtained by using leg force feedback in FMCH. This is in agreement with the implementation of VPP concept through FMCH and biarticular thigh actuation in simulated walking models [11] and a bipedal robot [54].…”
Section: Fmch Based Controller Has Higher Consistency In Emg Resposupporting
confidence: 89%
See 2 more Smart Citations
“…8 shows clear reductions in thigh biarticular muscles activities, obtained by using leg force feedback in FMCH. This is in agreement with the implementation of VPP concept through FMCH and biarticular thigh actuation in simulated walking models [11] and a bipedal robot [54].…”
Section: Fmch Based Controller Has Higher Consistency In Emg Resposupporting
confidence: 89%
“…The novel FMCH based controller reacts to human action within a bio-inspired control framework. Previous experimental and simulation studies have shown that FMCH is a feasible control concept for balance [10], [11]. Here, we found that the exoskeleton can assist human by using the same feedback design.…”
Section: Fmch Based Controller Has Higher Consistency In Emg Resposupporting
confidence: 51%
See 1 more Smart Citation
“…A Figura 3.1 mostra o fluxo de informações necessárias para produzir o andar. (Sharbafi et al, 2017).…”
Section: Visão Geral Do Movimentounclassified
“…Resumidamente , a marcha humana possui 3 sub-funções: função apoio, que ocorre através do contato com o solo de maneira oposta à gravidade; função de balanço, por meio da rotação da perna contralateral, com um pequeno movimento axial para evitar o contato com o solo; função equilíbrio, que ocorre para garantir a estabilidade ao andar, uma vez que a maior parte da massa do corpo está no dorso, tornando-se naturalmente instável (Sharbafi et al, 2017).…”
Section: Visão Geral Do Movimentounclassified